Lay People Representations on the Common Good and Its Financial Provision. (October 2018) - Castiglioni, Cinzia; Lozza, Edoardo; Bosio, Albino Claudio
The financial contribution to the common good is a relevant issue to contemporary societies, especially in the wake of the Global Financial Crisis. In the economic literature, taxes and monetary donations have been regarded as two complementary ways of financially providing for the common good. In the psychological literature, instead, they have not been studied in conjunction. In-depth interviews have been conducted using interpretative phenomenological analysis (IPA) approach and a photo-elicitation technique to investigate the representations people share on the financial provision for the common good. Results suggest that both taxes and donations are seen as indirect, rather than direct, ways of providing for the common good. From a formal and cognitive level, paying taxes and making donations can be seen as two sides of the same coin, but they present differences at the affective level. When paying taxes, people are concerned mostly about the effects and expect a material exchange in return; when making a monetary donation, people are concerned mostly about the motivations and expect an emotional exchange in return.